Rare Diseases Diagnostic and Therapeutic Odyssey - Valarmathi, Mani T. (IntechOpen, 2021)
A rare disease is any disease or condition that affects a small percentage of the population. Many rare conditions are life-threatening or chronically debilitating, and unfortunately do not have appropriate treatments, rendering them incurable. In recent years, there has been substantial development in the area of rare disease research and its clinical applications, for instance, rare disease biology and genomics, epidemiology and preventions, early detection and screening, and diagnosis and treatment. In this context, this book consolidates the recent advances in rare disease biology and therapeutics, covering a wide spectrum of interrelated topics, and disseminates this essential knowledge in a comprehensible way to a greater scientific and clinical audience as well as patients, caregivers, and drug and device manufacturers, especially to support rare disease product development. Chapters cover such diseases as Felty's syndrome, Löfgren's syndrome, mesothelioma, epidermolysis bullosa, and more. This book is a valuable resource not only for medical and allied health students but also for researchers, clinical and nurse geneticists, genetic counselors, and physician assistants.